Wall Paintings in Ancient Cyprus: The Hellenistic and Roman Tombs of Paphos and Its Region - Lysandrou, Vasiliki; Michaelides, Demetrios (Études et Travaux, 2021)
This paper presents the wall paintings decorating a number of Hellenistic and Roman tombs, of various architectural types, in Paphos and the region. The paper gathers together for the first time all the known published and unpublished painted tombs of the city, which are studied on the basis of observations made on the actual decoration preserved either in situ or in the laboratory of the Paphos District Museum, and with the use of all pertinent publications. A catalogue of these tombs has been created and this is accompanied by a map with the geographic location of each example. The various themes represented on wall paintings have been divided into groups and are discussed accordingly, while the manufacturing technology of a sample of the wall paintings is examined using both non-contact and analytical tools.